Radioimmunoassay and characterization of ligandin in the rat - Bass, Nathan Micahel (Department of Medicine, 2026)
Ligandin, a major soluble hepatic protein with the distinctive property of binding a wide range of organic anions, is a relative newcomer to the field of hepatic physiology and biochemistry, and its importance in relation to various aspects of hepatic and renal function has been given considerable stress (1-13).